Incorporating biodegradation and advanced oxidation processes in the treatment of spent metalworking fluids - MacAdam, Jitka; Ozgencil, Haci; Autin, Olivier; Pidou, Marc; Temple, Clive; Parsons, Simon A.; Jefferson, Bruce (Taylor & Francis, 2012)
The treatment of spent metalworking fluids (MWFs) is difficult due to their complex and variable composition. Small businesses often struggle to meet increasingly stringent legislation and rising costs as they need to treat this wastewater on site annually over a short period. Larger businesses that treat their wastewater continuously can benefit from the use of biological processes, although new MWFs designed to resist biological activity represent a challenge. A three-stage treatment is generally applied, with the oil phase being removed first, followed by a reduction in COD loading and then polishing of the effluent's quality in the final stage. The performance of advanced oxidation processes (AOPs), which could be of benefit to both types of businesses was studied. After assessing the biodegradability of spent MFW, different AOPs were used (UV/H2O2, photo-Fenton and UV/TiO2) to establish the treatability of this wastewater by hydroxyl radicals (•OH). The interactions of both the chemical and biological treatments were also investigated. The wastewater was found to be readily biodegradable in the Zahn–Wellens test with 69% COD and 74% DOC removal. The UV/TiO2 reactor was found to be the cheapest option achieving a very good COD removal (82% at 20min retention time and 10Lmin−1 aeration rate). The photo-Fenton process was found to be efficient in terms of degradation rate, achieving 84% COD removal (1M Fe2+, 40M H2O2, 20.7Jcm−2, pH 3) and also improving the wastewater's biodegradability. The UV/H2O2 process was the most effective in removing recalcitrant COD in the post-biological treatment stage.